Complement and sepsis-induced heart dysfunction. (April 2017) - Fattahi, Fatemeh; Ward, Peter A.
Highlights: Cardiomyopathy is a common complication of sepsis, often with a high mortality rate. Cardiomyopathy has requirements for complement C5a and its receptors. Molecular defects in cardiac dysfunction of sepsis are complement-dependent and develop during early sepsis. Cardiac dysfunction of sepsis disappears after recovery from sepsis, indicating cardiac dysfunction in sepsis is reversible. Presence of C5a receptors on surfaces of human CMs implies that CMs may respond to complement products. Abstract: It is well known that cardiac dysfunction develops during sepsis in both humans and in rodents (rats, mice). These defects appear to be reversible, since after" recovery" from sepsis, cardiac dysfunction disappears and the heart returns to its function that was present before the onset of sepsis. Our studies, using in vivo and in vitro models, have demonstrated that C5a and its receptors (C5aR1 and C5aR2) play key roles in cardiac dysfunction developing during sepsis. Use of a neutralizing antibody to C5a largely attenuates cardiac dysfunction and other adverse events developing during sepsis. The molecular basis for cardiac dysfunctions is linked to generation of C5a and its interaction with C5a receptors present on surfaces of cardiomyocytes (CMs). It is established that C5a interactions with C5a receptors leads to significant reductions involving faulty contractility and relaxation in CMs. In addition, C5a interactions with C5a receptors on CMs results in reductions in Na + /K + -ATPase in CMs. This ATPase is essential for intact action potentials in CMs. The enzymatic activity and protein for this ATPase were strikingly reduced in CMs during sepsis by unknown mechanisms. In addition, C5a interactions with C5aRs also caused reductions in CM homeostatic proteins that regulate cytosolic [Ca 2+ ]i in CMs: sarco/endoplasmic reticulum Ca 2+ -ATPase2 (SERCA2) and Na + /Ca 2+ exchanger (NCX). In the absence of C5a receptors, defects in SERCA2 and NCX in CMs after sepsis are strikingly attenuated. These observations suggest new strategies to protect the heart from dysfunction developing during sepsis.